Customer restaurant choice: an empirical analysis of restaurant types and eating-out occasions - Chua, Bee Lia; Ab Karim, Muhammad Shahrim; Lee, Sanghyeop; Han, Heesup (Multidisciplinary Digital Publishing Institute, 2020)
This study investigated restaurant customers’ perceived importance of key factors in accordance with dining occasions and restaurant segments. Our investigation into restaurant selection and situational factors present two types of empirical evidence regarding customers’ choice of restaurant. First, menu price was customers’ top priority in restaurant selections for full-service, quick-casual, and quick-service restaurants. Second, restaurant customers rated the importance level of restaurant selection criteria differently according to eating-out occasions. The importance of menu price was greatest for both quick meal/convenience and social occasion, brand reputation was the most important factor for business necessity, and word-of-mouth recommendation was greatest for celebration.